Development of Underground Mine Communication and Monitoring System by Using ZigBee Technology - Kawamura, Youhei; Moridi, Mohammad; Sharifzadeh, Mostafa; Jang, H. (JCRM, 2014)
Data transfer and communication systems are first priority for further development of geotechnical monitoring. This paper describes a Wireless Sensor Network (WSN) for communication and monitoring systems based on ZigBee technology in underground mines. Wireless sensor networks (WSNs) have been widely employed in industries and the military with multiple applications to monitor environment, track target and telecommunicate data. Recently, WSNs have also been used for communication and monitoring systems in underground mines. In this study, a proposed WSN system of ZigBee network as one of the WSNs is investigated in underground mines regarding communication and monitoring systems to resolve operational challenges such as safety and gathering geotechnical information. Developed ZigBee wireless network system was installed in Paddington Gold Underground Mine (managed by Norton Gold Fields Limited). In this research, the intensity of received signal strength indication (RSSI) between wireless nodes within ZigBee network was investigated. Also, the optimal arrangement of ZigBee wireless nodes on the basis of radio wave attenuation and possibility of stable wireless communications which will be used for gathering some significant geotechnical information such as seismic, deformation and pressure were investigated. The experimental results indicate that a secure and stable ZigBee wireless network can be developed to overcome mentioned operational challenges in underground mining. It is obvious that this proposed system helps further progress in rock mechanics and geotechnical fields